2003
DOI: 10.1002/ajhb.10229
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of eight molecular markers associated with thrombotic diseases in six Amerindian tribes and two African groups of Costa Rica

Abstract: Individuals belonging to six different Amerindian tribes and two African groups of Costa Rica were genotyped for factor V Leiden (FV), factor V haplotype HR2 (FV HR2), Factor II 20210G>A (FII), the methylenetetrahydrofolate reductase (MTHFR), factor VII polymorphisms (FVII IVS7, FVII R353Q), factor XIII (FXIII V34L), and the insertion/deletion (I/D) polymorphism of the gene of angiotensin converting enzyme (ACE). Clear differences in the prevalence were found and are first reported. The prevalence of some of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
1
5
0
3
Order By: Relevance
“…18,22,23 The FXIII Val34Leu polymorphism was confirmed as a protective factor against the occurrence of VT in this study. The homozygous Leu genotype was significantly more prevalent among controls than cases.…”
supporting
confidence: 66%
“…18,22,23 The FXIII Val34Leu polymorphism was confirmed as a protective factor against the occurrence of VT in this study. The homozygous Leu genotype was significantly more prevalent among controls than cases.…”
supporting
confidence: 66%
“…Likewise, in a study conducted in Chile (N = 1200), only 1% of the population had any variant alleles (Palomo et al, 2009). These variants are also rare in African, Chinese, and American Indian populations (Herrmann et al, 2004;Jun et al, 2006). On the other hand, they are common in Arab countries, with frequencies as high as approximately 11% for FV G1691A and 5% for FII G20212A (P < 0.001), as observed by Hussein (2012) in a Palestinian population.…”
Section: Discussionmentioning
confidence: 87%
“…In Mexico, for instance, the highest recorded frequency of 677T is 57%. Through analysis of indigenous tribes of Costa Rica, Herrmann et al (2004) found that the 677T allele was present in 69% of the population, the current highest observed prevalence of this polymorphism in the world. The high frequency of this polymorphism in the Asian countries Japan (40%) and Korea (44%) (Matsuo et al, 2004;Woo et al, 2009) were significantly different from the frequency found in this study (P = 0.003 and P = 0.011, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…FV HR2 was tested using a method modified in our laboratory (unpublished data). An extensive literature review for worldwide distribution of these factors was made [2–11].…”
Section: Results Of Dna Tests In a Healthy Saudi Arabian Populationmentioning
confidence: 99%